Stories of Teaching Race, Gender, and Class: A Narrative - Brenda V. Smith (Washington University Journal of Law & Policy, 2016)
This Essay transcribes and discusses Smith’s keynote speech at the New England Clinical Conference at Harvard Law School in November, 2015. Smith’s speech discusses the intersection between race, gender, and class, highlighting them as sites of vulnerability through a personal storytelling lens. By sharing her individual experiences, Smith hopes to draw attention to insecurities and threats faced by many individuals who refuse to speak out.
Keywords: Race; Gender; Class; Black Lives Matter; Women of color